1995
DOI: 10.1099/13500872-141-8-1805
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of regulatory mutants in photosynthesis gene expression in Rhodobacter sphaeroides 2.4.1 and partial complementation of a PrrB mutant by the HupT histidine-kinase

Abstract: The photosynthetic bacterium Rhodobacter sphaemides responds to the transition from aerobiosis to anaerobic photosynthesis by increasing the expression of the photosynthesis genes. Mutants have been isolated based on their inability, following such a transition, to increase transcription of the puc operon encoding the apoproteins of the light-harvesting complex II. Mutant D5, a representative of one mutant class, described here, although remaining photosynthetically competent, produced only low levels of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 39 publications
2
40
0
Order By: Relevance
“…The alteration in PrrB is then manifest by either an increase in histidine kinase activity or a decrease in phosphatase activity or any combination of the two, leading to the increase steady-state phosphorylated state of PrrA. Additionally, at least one (19) and possibly other (52) histidine kinases are capable of phosphorylating PrrA, which can normally be rendered noneffective in the presence of the PrrB-mediated phosphatase activity when oxygen is present.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The alteration in PrrB is then manifest by either an increase in histidine kinase activity or a decrease in phosphatase activity or any combination of the two, leading to the increase steady-state phosphorylated state of PrrA. Additionally, at least one (19) and possibly other (52) histidine kinases are capable of phosphorylating PrrA, which can normally be rendered noneffective in the presence of the PrrB-mediated phosphatase activity when oxygen is present.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the insertion mutation in PRRB2 was not polar to prrA and thus defined another coding sequence required for photosynthesis gene expression. Additionally, when multiple copies of prrA were placed in trans in PRRB2, the photosynthetic defect was bypassed, as might be anticipated since we have shown that prrA can be made active by at least one noncognate kinase, notably HupT (19). Therefore, the locus upstream of prrA was designated prrB, for photosynthetic response, regulator B.…”
mentioning
confidence: 95%
“…Cosmid pUI8714 was identified in the genetic screen for activators of PS gene expression in R. sphaeroides described previously (Gomelsky & Kaplan, 1995b). When provided in trans in the PrrB or PrrA null strains, it increased puc expression and pigmentation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Plasmid mobilization into R. sphaeroides and P. denitrificans was carried out from E. coli S17-1 as described previously (Gomelsky & Kaplan, 1995a) Construction of the PPA1 mutant. A deletion/substitution mutation in ppaA from R. sphaeroides 2.4.1 was constructed by replacing the internal NcoI fragment with an VKm r cartridge from pUI1637 (Gomelsky & Kaplan, 1995b) to generate plasmid p714BgHDNc : : Km (see Fig. 1b).…”
Section: Genetic Manipulationsmentioning
confidence: 99%
“…The presence of consensus-like PrrA DNA binding sites (15) in promoter regions of genes regulated by R. capsulatus RegA, for genes regulated under anaerobic conditions like ccoNOPQ and cycA (1,16), suggests that RegA and PrrA bind as dimers in all cases. RegA and PrrA might be able to form a dimer when unphosphorylated in the presence of a co-regulator, or might be activated by other kinases than their cognate histidine kinase (44).…”
Section: Discussionmentioning
confidence: 99%